Interleukin‐6 blockade with tocilizumab increases Tregs and reduces T effector cytokines in renal graft inflammation: A randomized controlled trial - Chandran, Sindhu; Leung, Joey; Hu, Crystal; Laszik, Zoltan G.; Tang, Qizhi; Vincenti, Flavio G. (American journal of transplantation, 2021)
Interleukin‐6 (IL‐6) is a proinflammatory cytokine and key regulator of Treg: T effector cell (Teff) balance. We hypothesized that IL‐6 blockade with tocilizumab, a monoclonal antibody to IL‐6R, would increase Tregs, dampen Teff function, and control graft inflammation. We conducted a randomized controlled clinical trial (2014–2018) of clinically stable kidney transplant recipients on calcineurin inhibitor, mycophenolate mofetil, and prednisone, with subclinical graft inflammation noted on surveillance biopsies during the first year posttransplant. Subjects received tocilizumab (8 mg/kg IV every 4 weeks; 6 doses; n = 16) or no treatment (controls; n = 14) on top of usual maintenance immunosuppression. Kidney biopsies pre‐ and post‐treatment were analyzed using Banff criteria. Blood was analyzed for serum cytokines, Treg frequencies, and T cell effector molecule expression (IFN‐γ, IL‐17, granzyme B) post‐stimulation ex vivo. Tocilizumab‐treated subjects were more likely to show improved Banff ti‐score (62.5% vs. 21.4%, p = .03), increased Treg frequency (7.1% ± 5.55% vs. 3.6% ± 1.7%, p = .0168), and a blunted Teff cytokine response compared to controls. Changes in Banff i‐ and t‐scores were not significantly different. The treatment was relatively well tolerated with no patient deaths or graft loss. Blockade of IL‐6 is a novel and promising treatment option to regulate the T cell alloimmune response in kidney transplant recipients. NCT02108600. In this single‐center, pilot, randomized controlled clinical trial of 30 kidney stable transplant recipients treated with either tocilizumab or no therapy for early subclinical graft inflammation, the authors report a significant increase in circulating regulatory T cells, a significant decrease in effector T cell function, and a trend toward improved graft inflammation with tocilizumab treatment.